The Influence of Exports and Imports on Economic Growth in Indonesia in 2001-2020 - Siburian, Rowinna; Anggraini, Angela; Tamba, Kioko; Cristina, Anju; Hasibuan, Adi Susanto; Umar, Andi Taufiq (LP2M IAIN Palopo, 2024)
The study uses an associative quantitative approach method which aims to determine the influence of exports and imports on economic growth both partially, and simultaneously, This research was carried out using several analyses and multiple regression tests, including the Classical Assumption Test and the Hypothesis Test to see the influence between variables. This study uses secondary data regarding related variables sourced from the Central Statistics Agency (BPS). The results of this study show that partially exports have a positive and significant. This result also explains that the higher the export, the more economic growth will increase, but on the contrary, if imports increase, economic growth will decrease. The benefits of global economic openness can be seen from the condition of a country's economic balance. Participation in import export activities will bring great benefits to the countries involved. In future research, it is important to dig deeper into how certain factors in exports and imports can have different impacts on economic growth.